The [4.3.0] Piperidine Alkaloids: Architectures, Biology, Biosyntheses, and the Complete Details of the Asymmetric Syntheses of Streptazone A and Abikoviromycin - Wørmer, Gustav J.; Poulsen, Thomas B. (Synlett, 2021)
Piperidine alkaloids continue to challenge the synthetic community by featuring densely functionalized scaffolds that often require careful chemical orchestration. Streptazone A and abikoviromycin are small and highly functionalized piperidine alkaloids, both accommodating Michael acceptors and a labile epoxide. These moieties are loaded into a [4.3.0] bicyclic core also present in other structurally related natural products, including the well-known piperidine alkaloid streptazolin. Here, we cover ring-closing strategies employed in earlier streptazolin syntheses; provide a concise overview of structures, biological properties, and biosyntheses of selected [4.3.0] piperidine alkaloids; and, finally, provide complete coverage of our recent asymmetric syntheses of streptazone A and abikoviromycin.1 Introduction2 Streptazolin Syntheses3 Epo-[4.3.0] Piperidine Alkaloids3.1 Streptazones3.2 Abikoviromycin3.3 Strepchazolin A and B3.4 Hatomamicin3.5 Kobutimycin A and B3.6 Camporidines A and B3.7 Epostatin3.8 N-Hydroxydihydroabikoviromycin3.9 Dihydroabikoviromycin3.10 Biosynthesis of Streptazone E and Camporidines4 Syntheses of the Streptazones and Abikoviromycin4.1 Retrosynthesis4.2 Results and Discussion5 Conclusion
Keywords: piperidine alkaloids; electrophilic natural products; total synthesis; asymmetric synthesis; Pauson–Khand cyclization; enaminone reduction